Mechanisms and significance of Ca2+ entry through TRPC channels. Issue 17 (October 2020) - Bacsa, Bernadett; Tiapko, Oleksandra; Stockner, Thomas; Groschner, Klaus
Highlights: 9/10: New and groundbreaking insights into TRPC Ca2+ signaling functions in the brain. 20/21: New study on the linkage of TRPC Ca2+ signaling to membrane lipid homeostasis in terms of phosphatidylserine exposure. 45: New, groundbreaking information on ligand coordination in TRPC channels. 58/59: Key studies presenting new concepts of lipid regulation of TRPC Ca2+ signaling. Abstract : The transient receptor potential (TRP) superfamily of plasma membrane cation channels has been recognized as a signaling hub in highly diverse settings of human physiopathology. In the past three decades of TRP research, attention was focused mainly on the channels Ca 2+ signaling function, albeit additional cellular functions, aside of providing a Ca 2+ entry pathway, have been identified. Our understanding of Ca 2+ signaling by TRP proteins has recently been advanced by a gain in high-resolution structure information on these pore complexes, and by the development of novel tools to investigate their role in spatiotemporal Ca 2+ handling. This review summarizes recent discoveries as well as remaining, unresolved aspects of the canonical subfamily of transient receptor potential channels (TRPC) research. We aim at a concise overview on current mechanistic concepts of Ca 2+ entry through- and Ca 2+ signaling by TRPC channels.